Traffic Sign Detection and Recognition Using TensorFlow' s Object Detection API with A New Benchmark Dataset - Kilic, Irfan; Aydin, Galip (Institute of Electrical and Electronics Engineers Inc., 2020)
In this study TensorFlow's Object Detection API used in Turkey traffic sign detection and recognition of the aid intended traffic signs. A dataset suitable for TensorFlow's Object Detection API has been prepared for traffic signs by using photographs in different traffic and weather conditions. A web-based data tagging application has been developed to prepare this dataset. This dataset was trained by selecting the appropriate deep learning model and results were obtained on the test data. Although the training data are insufficient, the results on the test images are satisfactory. © 2020 IEEE.
6th International Conference on Electrical Engineering, ICEE 2020 -- 25 September 2020 through 27 September 2020 -- Virtual, Istanbul -- 164956
Keywords: dataset; deep learning; object detection; TensorFlow; Tensorflow's Object Detection API; traffic signs